1998
DOI: 10.1016/s0378-1135(98)00210-7
|View full text |Cite
|
Sign up to set email alerts
|

Detection of feline coronaviruses by culture and reverse transcriptase-polymerase chain reaction of blood samples from healthy cats and cats with clinical feline infectious peritonitis

Abstract: A reverse transcriptase-polymerase chain reaction (RT-PCR) assay for the detection of the feline coronavirus (FCoV) genome and a co-cultivation method for the isolation of field strains of FCoV are described. Using the RT-PCR assay to assess blood samples from cats with feline infectious peritonitis (FIP) (n = 47) and healthy cats from households with endemic FCoV (n = 69) it was shown that approximately 80% of the cats were viraemic, irrespective of their health status. It was also shown that, over a 12-month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
104
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(111 citation statements)
references
References 21 publications
5
104
2
Order By: Relevance
“…Kobuvirus RNA was detected by RT-PCR using a broadly reactive primer pair, UNIV-kobu-F/UNIV-kobu-R (Reuter et al, 2009a), which amplifies a 217-bp fragment of the 3D region of all kobuvirus species. The samples were also tested by PCR or RT-PCR for feline parvovirus (FPV) (Buonavoglia et al, 2001) and feline enteric coronavirus (FECV) (Gunn-Moore et al, 1998).…”
Section: Screening By Rt-pcr and Pcr And Sequence Analysismentioning
confidence: 99%
“…Kobuvirus RNA was detected by RT-PCR using a broadly reactive primer pair, UNIV-kobu-F/UNIV-kobu-R (Reuter et al, 2009a), which amplifies a 217-bp fragment of the 3D region of all kobuvirus species. The samples were also tested by PCR or RT-PCR for feline parvovirus (FPV) (Buonavoglia et al, 2001) and feline enteric coronavirus (FECV) (Gunn-Moore et al, 1998).…”
Section: Screening By Rt-pcr and Pcr And Sequence Analysismentioning
confidence: 99%
“…28 Despite the generally high prevalence of FCoV infection among the cat population, especially in multicat facilities, FIP morbidity is low and rarely surpasses 5%. 1,7,28 FIP seems to develop in the individual infected animal when FCoV acquires virulence by deletions in open reading frames 3 and 7, coding for nonstructural proteins of unknown function, which occur as mutations primarily during replication in the infected host. 39 Most infected cats develop an FCoV viremia that can be detected by reverse transcriptase-polymerase chain reaction (RT-PCR) on isolated (and cultivated) monocytes regardless of the development of FIP.…”
mentioning
confidence: 99%
“…39 Most infected cats develop an FCoV viremia that can be detected by reverse transcriptase-polymerase chain reaction (RT-PCR) on isolated (and cultivated) monocytes regardless of the development of FIP. 7,15 FCoV- 1 Present address: Department of Veterinary Pathology, Faculty of Veterinary Science, University of Liverpool, Liverpool, UK infected circulating monocytes are considered as responsible for viral dissemination within the host. 10,11,28,44 Furthermore, the demonstration of FCoV antigen within intravascular leukocytes and among cells in the lesions of vasculitis in a previous experimental study suggested that the infected monocyte mediates the development of FIP lesions.…”
mentioning
confidence: 99%
“…15,37 Hyperproteinemia and polyclonal gammopathy (detected by electrophoresis; see Chapter 12) can occur, particularly in the noneffusive form. The most reliable means of identifying focal FeLV infections is virus isolation or PCR assay.…”
Section: Enteric Virusesmentioning
confidence: 99%